“Managing” Inaction and Public Disengagement with Climate Change: (Re)considering the Role of Climate Change Discourse in Compulsory Education - Daina, Erin; Davis, Kat (Javnost-The Public, 2023)
Discourse constitutes knowledge about something and the processes by which we come to know it. This is true in formal education and everyday life. In this way, both what students know about climate change and how they engage with publics about climate change are intertwined. Implementing teaching and learning about discourse in compulsory education is an opportunity to prepare young people to critically engage in public life by focusing on how to recognise and counter strategies that seek inaction as an appropriate response. In other words, by focusing on the strategies, impacts and effects of discourse in education about climate change, the ill effects of inaction associated with climate anxiety and climate fatigue can be “managed” in a long-term (re)imagination of an engaged public capable of working towards a sustainable, shared future. We contend that education about climate change discourse in global compulsory education curricula can provide young people opportunities to learn not only about climate change science, but about how to (re)consider discursive strategies used by others that otherwise promote and resist calls for action. This can produce a new generation of citizens capable, motivated and prepared to actively engage climate change discourse in public life.